Interacting climate change environmental factors effects on Fusarium langsethiae growth, expression of Tri genes and T-2/HT-2 mycotoxin production on oat-based media and in stored oats. Issue 8 (August 2019) - Verheecke-Vaessen, Carol; Diez-Gutierrez, Lucia; Renaud, Justin; Sumarah, Mark; Medina, Angel; Magan, Naresh
Abstract: This study examined the effect of climate change (CC) abiotic factors of temperature (20, 25, 30 °C), water activity (aw ; 0.995, 0.98) and CO2 exposure (400, 1000 ppm) may have on (a) growth, (b) gene expression of biosynthetic toxin genes ( Tri5, Tri6, Tri16 ), and (c) T-2/HT-2 toxins and associated metabolites by Fusarium langsethiae on oat-based media and in stored oats. Lag phases and growth were optimum at 25 °C with freely available water. This was significantly reduced at 30 °C, at 0.98 aw and 1000 ppm CO2 exposure. In oat-based media and stored oats, Tri5 gene expression was reduced in all conditions except 30 °C, 0.98 aw, elevated CO2 where there was a significant (5.3-fold) increase. The Tri6 and Tri16 genes were upregulated, especially in elevated CO2 conditions. Toxin production was higher at 25 °C than 30 °C. In stored oats, at 0.98 aw, elevated CO2 led to a significant increase (73-fold) increase in T2/HT-2 toxin, especially at 30 °C. Nine T-2 and HT-2 related metabolites were detected, including a new dehydro T-2 toxin (which correlated with T-2 production) and the conjugate, HT-2 toxin, glucuronide. This shows that CC factors may have a significant impact on growth and mycotoxin production by F. langsethiae .